2005
DOI: 10.1080/08035250500323780
|View full text |Cite
|
Sign up to set email alerts
|

The global obesity epidemic: Snacking and obesity may start with free meals during infant feeding

Abstract: We hypothesize that non-rule breastfeeding favours the development of snacking throughout the day during childhood, a habit which in turn favours the development of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 90 publications
(89 reference statements)
2
22
0
Order By: Relevance
“…For instance, Koletzko and colleagues have demonstrated that no differences in weight gain are seen in babies fed low-protein formula [119]. Maternal diet during lactation [and hence the content of the milk] [120] and even the frequency of feeding may also affect the baby's risk of developing obesity [121,122], as can the timing of the introduction of formula or solid food [123]. For instance, maintaining a diet of organic dairy and meat products increases the breast milk content of conjugated linoleic acid isomers [120].…”
Section: Postnatal Nutritionmentioning
confidence: 99%
“…For instance, Koletzko and colleagues have demonstrated that no differences in weight gain are seen in babies fed low-protein formula [119]. Maternal diet during lactation [and hence the content of the milk] [120] and even the frequency of feeding may also affect the baby's risk of developing obesity [121,122], as can the timing of the introduction of formula or solid food [123]. For instance, maintaining a diet of organic dairy and meat products increases the breast milk content of conjugated linoleic acid isomers [120].…”
Section: Postnatal Nutritionmentioning
confidence: 99%
“…Among alimentary behaviors, snacking activity has been identified as one potential cause of obesity and/or overweight in childhood and adolescent [7]. Following Hampl [8], a child who's getting more than 15-20% of his/her daily caloric intake from snacks can be defined as a "snacker".…”
Section: Introductionmentioning
confidence: 99%
“…High-fat diet has been associated as a major factor causing obesity where as some foods like whole grains, vegetables, fruits and nuts are categorized as weight-control foods [64,65]. Few probable ways by which diet affects body weight are control of satiety and metabolic efficiency, or modulation of insulin secretion and action [66].…”
Section: Patents In the Field Of Medicine Fat Metabolism And Obesitymentioning
confidence: 99%